PERAN LITERASI KEUANGAN DALAM MENINGKATKAN PEMBANGUNAN EKONOMI MASYARAKAT DESA - I G.A.N Alit Sumantri; I Gusti Agung Ayu Pramita Indraswari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
. Knowledge of literacy is very important because the growth of financial products is very fast and easily accessible to everyone. Financial literacy is knowledge, skills and beliefs that can influence individual attitudes and behavior. People who are aware of financial literacy or are financially intelligent can understand financial planning, so they can make financial decisions to achieve their financial goals. Meanwhile, financial inclusion is an important part of social economics, namely inclusiveness towards high financial access for all levels of society in a country can encourage economic growth, financial system stability, poverty alleviation initiatives, as well as an effort to reduce the community's economic decline. The community in Paksebali Village is expected to understand the importance of financial literacy in the businesses they run. Along with the need for financial literacy experienced by MSME entrepreneurs, financial management is still minimal and often experiences problems in the field. This is due to the lack of basic knowledge of financial management and limited knowledge of financial literacy